Quantification, molecular characterization and aggressiveness of Ralstonia solanacearum species complex in Eucalyptus spp. - Freitas, Rodrigo Galvão de (2021)
Bacterial wilt caused by Ralstonia solanacearum is a serious disease of eucalypt in humid and high temperature areas worldwide. The bacterium exhibits considerable variation in the host range, geographic origin, pathogenicity and physiological properties. Spreading of the bacterium in the field or to other eucalypt nurseries occurs mainly by infected but asymptomatic plant material. The use of pathogen-free propagating material as well as planting of resistant genotypes are currently the only strategies used for the disease control. Therefore, knowledge of the phylotype composition and genetic variability in populations of this bacterium is useful for implementing effective control measures. In this work, we developed an efficient intercalating dye-based real-time PCR protocol to detect the bacterium in asymptomatic eucalypt plants as well as to investigate its movement in tissues of clones with different levels of resistance. In addition, we identified phylotypes, sequevars and genotypes of 93 Ralstonia isolates, obtained from cuttings and eucalypt trees grown in different regions of Brazil. Subsequently, sequevar distribution patterns and their relationship with the aggressiveness of the bacterium in eucalypt clones were investigated. Through the real-time PCR technique, we found that the bacterium translocates acropetally and basipetally in inoculated but asymptomatic plants of the resistant clone as in plants of the symptomatic susceptible one. Nevertheless, a lower bacterial concentration was detected in the tissues of the resistant clone, where, through the scanning electron microscope, no bacterial biofilm was observed obstructing the xylem vessels. With the molecular characterization, we found that, like R. solanacearum (phylotype II), R. pseudosolanacearum (phylotype I) also causes eucalypt wilt. However, R. pseudosolanacearum is genetically uniform, which indicates a probable recent introduction of this phylotype in the country. Unlike R. pseudosolanacearum, R. solanacearum is phylogenetically diverse, and there is no correlation between sequevar and geographic origin. Isolate aggressiveness varied between the eucalypt clones tested, reinforcing the importance of conducting molecular and aggressiveness characterizations of the pathogen population, in order to support the selection of resistant material. The qPCR method developed in this study could be valuable for pathogen detection during disease diagnosis as well as pathogen quantification in plant tissue. The present study expands the knowledge of the variability of the Ralstonia solanacearum species complex in Eucalyptus spp. Keywords: Bacterial wilt. Real time PCR. Eucalypt.